Evaluation of CD30/CD4/CD8 in triple-negative invasive ductal carcinoma of breast in association with clinicopathological prognostic factors - Amir Hossein Jafarian; Aida Tasbandi; Hamed Gilan; Maryam Sheikhi; Nema Mohamadian Roshan (Wolters Kluwer Medknow Publications, 2018)
Background: Triple-negative breast cancer (TNBC) lacks the benefits of receptor-targeted therapeutic strategies. The limitations in treatment options along with poor patients' outcome heighten the need for novel approaches. Due to recent concentration on the role of biomarkers in prognosis, treatment, and survival of various cancer subtypes, this study involves an investigation of CD4, CD8, and CD30 markers detected by immunohistochemistry in TNBCs and their association with clinicopathological and prognostic factors. Materials and Methods: Tissue samples of 85 hormone receptor- and human epidermal growth factor receptor-2-negative ductal breast carcinomas extracted from the archive of pathology department. Regarding CD4/CD8 ratio, the infiltrated T-lymphocytes were investigated. The tumoral tissue regions were also identified to be immunohistochemically assessed for the CD30 expression levels. Results: With an elevated CD4/CD8 ratio, a significant increase in lymph node involvement was observed (P < 0.05); in contrast, increased expression levels of CD8 were related to significant reduction of lymph node involvement. CD30 overexpression was found to be significantly associated with shortened overall survival (OS) and highly involvement of lymph nodes. Conclusion: Following the progression in stage and grade of tumor, CD4/CD8 ratio and CD30 expression levels are increased and are accompanied by adverse prognosis and poor OS, while CD8-enhanced expression carries a favorable prognostic impact as it improves OS status. Therefore, all these findings could be of interest in the field of target therapy.